BINA KELUARGA REMAJA (BKR) DALAM RANGKA MENINGKATKAN POLA ASUH REMAJA YANG BENAR DAN TERARAH - Fajar Hidayanto (Asian Journal of Innovation and Entrepreneurship, 2015)
Family the first and top learning place for every teenager. Parenting way will affectthe development of teenager's characters. But, not all parents understand how to dealwith teenager correctly, such as parents at Dusun Jati, Kelurahan Gerbosari, KecamatanSamigaluh, Kabupaten Kulon Progo, Provinsi D.I. Yogyakarta. So, they need an educationabout parenting. Based on these circumstances, the authors organized a " Bina KeluargaRemaja (BKR)" as a community service activities. Parents are given educational materialin six sessions, those are definition of teenager, the importance of parents role, theimportance of sex education for teenager, the importance of parental supervision, therole of peers, and the role of parents to help tenageer to recognize himself. The serviceactivities managed to increase the knowledge of parents in tenaager growth fosteringcorrectly and focused, in order to build a quality family.